2013
DOI: 10.1038/ni.2633
|View full text |Cite
|
Sign up to set email alerts
|

The signaling suppressor CIS controls proallergic T cell development and allergic airway inflammation

Abstract: Transcription factors of the STAT (signal transducer and activator of transcription) family are critical in the cytokine-mediated functional differentiation of CD4 + helper T cells. Members of the SOCS (suppressor of cytokine signaling) family negatively regulate the activation of STAT proteins; however, their roles in the differentiation and function of helper T cells are not well understood. Here we found that the SOCS protein CIS, which was substantially induced by interleukin 4 (IL-4), negatively regulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
123
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(130 citation statements)
references
References 69 publications
6
123
0
1
Order By: Relevance
“…Therefore, the level of pSTAT3 in monocytes likely reflects the sum of diverse inflammatory stimuli targeting STAT3. Consistent with these observations, the phosphorylation levels of STAT3 and other STAT proteins have been found to be increased in asthma (30) and in other inflammatory conditions (31). With respect to the influenza vaccine response, our results indicate that the natural variation in circulating free testosterone could drive many of the differences observed in the response to vaccines.…”
Section: Discussionsupporting
confidence: 76%
“…Therefore, the level of pSTAT3 in monocytes likely reflects the sum of diverse inflammatory stimuli targeting STAT3. Consistent with these observations, the phosphorylation levels of STAT3 and other STAT proteins have been found to be increased in asthma (30) and in other inflammatory conditions (31). With respect to the influenza vaccine response, our results indicate that the natural variation in circulating free testosterone could drive many of the differences observed in the response to vaccines.…”
Section: Discussionsupporting
confidence: 76%
“…In particular, skin inflammation is strongly regulated by SOCS1 and SOCS3, as SOCS3 deficiency in keratinocytes causes severe skin inflammation, whereas keratinocyte-specific SOCS1 overexpression down-regulates the expression of specific pro-inflammatory mediators in the skin (30). In the context of type 2 inflammation, the SOCS family member cytokine-inducible SH2-containing protein (CIS) has recently been shown to regulate pro-allergic T helper cell development and to control allergic inflammation (31). In this study, we demonstrated that IL-31 is able to enhance the expression of SOCS1, SOCS2, SOCS3, and CISH in a time-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…SOCS proteins then provide feedback inhibition by binding to cytokine receptors and JAK kinases. Accordingly, mutations of SOCS1 (100-102) and SOCS3 (103-105) have major effects on erythropoiesis, the immune system, and the placenta, while CISH deletion also affects immunity but in a more subtle way (106).…”
Section: Cell Regulation By Socs-crl5 Complexes and By Socs Proteins mentioning
confidence: 99%